Six sigma DMAIC approach in a modern rubber factory - Leneesh N, Gopal; Harikrishnan; Jose, Arun; Jishnu (International Journal of Computer Sciences and Engineering, 2025)
The objective of this paper is to present a review of six sigma DMAIC Methodology (D-Define, M-Measure, A- Analyses, I- Improve and C-Control). The papers containing DMAIC in their titles were collected and studied during this literature review. The results of the studies reported in this paper have confirmed that DMAIC is a compatible model for the benefit of the Six Sigma concepts in the manufacturing sector. In this background, this paper has been concluded by suggesting future research to examine the application of DMAIC in many areas.